(untitled) (Research, Society and Development, 2020)
The incorporation of basalt powder as a way to promote soil recovery is a current challenge. The work was oriented to evaluate the development of soybean cultivars (SC) after the superficial application of different doses of basalt powder (DBP) in the soil. The experimental delineation used was that of randomized complete blocks, with 3 × 4 factorial arrangement, with three replicas. The treatments were the combination of three SC and four DBP (0, 1, 3 and 5 t ha-1). In the harvest the height of the plants (HP), insertion of the first pod (IFP), number of pods per plant (NPP), number of grains per pod (NGP), mass of one thousand grains (MTG) and yield were determined. of experimental plots (REND). With the harvested grains, they were classified by size in seven sieves of different diameter (Ø7.5 - Ø4.5 mm) and the percentage and relative productivity of grains retained in mesh (RPGRM) were calculated. The results pointed to significant interactions (SC x DBP) (P<0.01) for the variables height of the plants, number of pods per plant and percentage of grains retained in the sieve Ø6.5; with variable responses between the cultivars and the doses used for these three variables. The doses of basalt powder did not influence the performance of soybean cultivars, but contributed to obtaining a better seed size and thus improved the quality of the seeds obtained.